MSME Development Through Packaging Design, Labels and Trademark Registration - Fadhilah, Eka Yuli Astuti; Fadhilah, Rahma; Putri, Yessa Meidina; Anjani, Ayu Sri; Azkia, Zahratul; Hasanah, Alfiyah Nurul; Saharani, Silvi Intan; Fauziah, Silva; Sintawati, Cucu; Lesmana, Indra (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The MSME sector plays an important role in the development of the national and regional economy. MSMEs can increase income, reduce unemployment rates in villages and can increase entrepreneurial experience. Mekarsari Village has a variety of MSMEs which have great potential to improve community welfare. However, the problem faced by MSME in Mekarsari Village is a lack of knowledge about creating packaging designs, labels and registering trademarks to protect intellectual property rights. The aim of this service is to provide assistance in creating and updating packaging and labels so that the products produced are more attractive and have a higher selling price, as well as providing knowledge about how to register trademarks so they can compete with competitors. The methods used in this service are direct observation, interviews and discussions and implementation. The results obtained from this service are the creation of understanding among MSME players in Mekarsari village about how to make packaging and labels so that the products produced are more innovative. This service also increases the legal awareness of the MSME community regarding the importance of registering trademarks and how to register these brands.